Patient and practice level factors associated with consultation duration: a cross-sectional analysis of over 1 million consultations in English primary care - Stevens, S; Bankhead, C; Mukhtar, T; Perera-Salazar, R; Holt, T; Salisbury, C; Hobbs, F (BMJ Publishing Group, 2017)
Objectives: Consultation duration has previously been shown to be associated with patient, practitioner, and practice characteristics. However, previous studies were conducted outside the UK, considered only small numbers of GP consultations, or focused primarily on practitioner level characteristics. We aimed to determine the patient and practice level factors associated with duration of GP and nurse consultations in UK primary care. Design and setting: Cross sectional data were obtained from English general practices contributing to the Clinical Practice Research Datalink (CPRD) linked to data on patient deprivation and practice staffing, rurality, and Quality and Outcomes Framework (QOF) achievement. Participants: 218,304 patients, from 316 English general practices, consulting from 1st April 2013 to 31st March 2014. Analysis: Multilevel mixed effects models described the association between consultation duration and patient and practice-level factors (patient age, gender, smoking status, ethnic group, deprivation and practice rurality, number of full time equivalent GPs/nurses, list size, consultation rate, quintile of overall QOF achievement, and training status). Results: Mean duration of face-to-face GP consultations was 9.24 minutes and 5.32 minutes for telephone consultations. Nurse face-to-face and telephone consultations lasted 9.70 and 5.73 minutes on average, respectively. Longer GP consultation duration was associated with female patient gender, practice training status and older patient age. Shorter duration was associated with higher deprivation and consultation rate. Longer nurse consultation duration was associated with male patient gender, older patient age and ever smoking; and shorter duration with higher consultation rate. Observed differences in duration were small (e.g. GP consultations with female patients compared to male patients were 8 seconds longer on average). Conclusions: Small observed differences in consultation duration indicate that patients are treated similarly regardless of background. Increased consultation duration may be beneficial for older or comorbid patients, but the benefits and costs of increased consultation duration require further study.